(untitled) (Global Media Journal - German Edition, 2023)
Trust, a key ingredient for the functioning and survival of the media, has been gradually eroding in the Czech Republic and Slovakia. This essay argues that while some sources of that decline stem from broader social and cultural factors, others can be found in the media and journalists themselves. In both countries, the key reasons seem to be similar: commercialization and oligarchization have given rise to a sceptical attitude towards the media and journalists and it has generated suspicion that they act in the interests of economic and political actors rather than in the interest of the public. In addition, the rise of “alternative” media that spreads disinformation, hoaxes, and propaganda, together with attacks against journalists by top political representatives, further stimulate and strengthen the public perception that journalists are biased and corrupt, and that the media cannot be trusted. The more pronounced decline in trust observed in Slovakia can be explained by lower institutional trust at the societal level, the suspected greater inclination of Slovak journalists towards activism, weaker public service media and its less stable position, and a smaller market that may make it more difficult for various social groups to find a media outlet to represent them.